The Hydrological Comparisions Between The Chalk Aquifer and The Holderness Glacial Till of Small Catchwater Drain Catchment in Holderness, England. - Sulaiman Zaidky, Ramadhan H. (Science Journal of University of Zakho, 2014)
The research programme was about the hydrology of this part of Holderness, particularly in respect of the interactions between superficial and deeper hydrological system, in order that the long term findings from the Catchwater Drain catchment might be more usefully applied to the solution of hydrological problems, including agricultural water supplies, land drainage, flooding and need for irrigation.There has been no attempt, however, in previous work to quantify the hydrological relationships between the clay and sand/gravel areas of the catchment or even to determine precisely the geographical extent of the sand/gravel layers and lenses. In the early studies, the assumption made was that the catchment was hydrologically watertight. This research has resolved a number of outstanding uncertainties which have raisin during the long period of operation of the Catchwater Drain catchment and that it has shed valuable new light on the hydrology, not only of the Catchwater Drain catchment but also of the glacial till of Holderness.It is to be hoped that the improved understanding which has thereby resulted will be of value in the interpretation of the hydrological behaviour of extensive, similar areas elsewhere.